2014
DOI: 10.11002/kjfp.2014.21.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effect of Polygala tenuifolia

Abstract: This study was performed in order to investigate the anti-obesity effect of Polygala tenuifolia on lipid mechanism in 3T3-L1 adipocytes. The chemical composition of the P. tenuifolia was analyzed in order to assess its nutritional value. Total dietary fiber was the highest among the proximate component of the P. tenuifolia. These results showed that the P. tenuifolia may be used as a potential functional ingredient for anti-obesity effect. Intracellular lipid droplets in the adipocyte were stained with oil-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As shown in Figure 3, these were inhibited during the 1.0 mg/mL treatment by 1.52, 1.81, 1.13, and 1.18 times, respectively, compared to the control group. The inhibition of CEBP-α expression in preadipocytes via CHE treatment was 2.2 times higher than that reported in Lee et al, where it was demonstrated that the inhibition of preadipocyte differentiation produced anti-obesity effects (Hwang et al, 2014). Additionally, Wang et al (1995) confirmed that lipid accumulation did not occur when CEBP-α was eliminated from the in vivo model, further demonstrating that the inhibition of this gene is essential to obtain the antiobesity effect as it upregulates preadipocyte differentiation (Wang et al, 1995).…”
Section: Effect Of Che On Anti-obesity Gene Expressionmentioning
confidence: 69%
“…As shown in Figure 3, these were inhibited during the 1.0 mg/mL treatment by 1.52, 1.81, 1.13, and 1.18 times, respectively, compared to the control group. The inhibition of CEBP-α expression in preadipocytes via CHE treatment was 2.2 times higher than that reported in Lee et al, where it was demonstrated that the inhibition of preadipocyte differentiation produced anti-obesity effects (Hwang et al, 2014). Additionally, Wang et al (1995) confirmed that lipid accumulation did not occur when CEBP-α was eliminated from the in vivo model, further demonstrating that the inhibition of this gene is essential to obtain the antiobesity effect as it upregulates preadipocyte differentiation (Wang et al, 1995).…”
Section: Effect Of Che On Anti-obesity Gene Expressionmentioning
confidence: 69%
“…Recently, bioactive compounds have been extensively studied, and provide not only essential roles as nutrients but also biochemical and pharmacological functions beneficial to human health [ 43 ]. In previous studies, Polygala genus plants have been reported to possess anti-obesity effects [ 29 , 44 ]. However, there are no studies on the anti-obesity activities and mechanisms of PC isolated from P. japonica Houtt.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it inhibits pre-adipocyte differentiation and adipogenesis by blocking sterol regulatory element-binding protein-1c (SREBP-1c) gene expression in 3-day transfer, inoculum 3 × 10 5 cells (3T3-L1) cells. Therefore, Polygala tenuifolia can be used as an effective anti-obesity agent [ 18 ] Radix polygalae extract can protect against N-methyl D-aspartate (NMDA) neurotoxicity and induced brain-derived neurotrophic factor expression, suggesting modulatory roles at glutamatergic synapses and possible anti-depressant action [ 19 ]. Curcuma longa extracts can have anti-cancer activities [ 20 ] and also have higher radical scavenging activities and anti-inflammatory effect [ 21 ].…”
Section: Discussionmentioning
confidence: 99%